The Russo - Japanese War and the Japanese Factor in the Development of the Vietnamsese Nationalist Movement in the Early 20th Century - Tung, Pham Hong (VNU Journal of Science: Social Sciences and Humanities; Vol 21 No 4E, 2005)
Abstract